Dissipativity-Based Stability Analysis of Networked Nonlinear Descriptor Systems and Its Application to Power Grids. Issue 1 (1st January 2019) - Kojima, Chiaki; Susuki, Yoshihiko; Hara, Shinji
Abstract : This paper pursues to construct a theoretical framework which can efficiently capture the dynamics of large-scale heterogeneous power grids. We formulate a networked nonlinear descriptor system consisting of subsystems and network system as a mathematical abstraction of such grids. This descriptor representation of the system enables us to consider efficient analysis and control of the system while preserving its network topology. As a main result, we clarify the dissipativity of the systems and derive a sufficient condition for local asymptotic stability of partial states and synchronization based on the dissipativity. We apply these results to a power grid described by a structure-preserving model, showing their effectiveness in an engineering problem.